Ciclos e letramento na fase inicial do ensino fundamental - Creso Franco (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2004)
The article presents and criticises the sources that provide elements for measuring the relative prevalence of the organisation of schooling in cycles in the Primary Education in Brazil. It discusses perspectives that solve methodological problems present in many surveys that make use of those sources. Also, based on those sources, it describes the recent status of the policies implanted in the State and Municipal Secretaries in the Brazilian capital cities. With reference to cycles in the early years of Primary Education, it discusses the potentials and limits of quantitative research that try and evaluate the impact of cycles in Brazilian education.